2012
DOI: 10.1016/j.cmet.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

BBS-Induced Ciliary Defect Enhances Adipogenesis, Causing Paradoxical Higher-Insulin Sensitivity, Glucose Usage, and Decreased Inflammatory Response

Abstract: Studying ciliopathies, like the Bardet-Biedl syndrome (BBS), allow the identification of signaling pathways potentially involved in common diseases, sharing phenotypic features like obesity or type 2 diabetes. Given the close association between obesity and insulin resistance, obese BBS patients would be expected to be insulin resistant. Surprisingly, we found that a majority of obese BBS patients retained normal glucose tolerance and insulin sensitivity. Patient's adipose tissue biopsies revealed upregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
102
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(106 citation statements)
references
References 66 publications
3
102
1
Order By: Relevance
“…The present data suggest that a single PO challenge promotes pathways of LPSand TLR4-mediated inflammation and cytotoxicity, which are buffered by the activation of NF-κB, which in turn contributes to insulin resistance. This study also found altered regulation of other putative cytoprotective mechanisms including the phospholipase C4 pathway, which is important for hepatic regeneration (54), and PPARα, which serves as both a canonical pathway and an upstream regulator protecting against NAFLD progression (29).…”
Section: Figure 2 Time Courses Of Circulating Metabolites and Hormonmentioning
confidence: 84%
“…The present data suggest that a single PO challenge promotes pathways of LPSand TLR4-mediated inflammation and cytotoxicity, which are buffered by the activation of NF-κB, which in turn contributes to insulin resistance. This study also found altered regulation of other putative cytoprotective mechanisms including the phospholipase C4 pathway, which is important for hepatic regeneration (54), and PPARα, which serves as both a canonical pathway and an upstream regulator protecting against NAFLD progression (29).…”
Section: Figure 2 Time Courses Of Circulating Metabolites and Hormonmentioning
confidence: 84%
“…In contrast to BBS10 and BBS12, knockdown of ALMS1 (mutated in ALMS) in 3T3-L1 inhibited adipogenesis [135]. Depletion of the ciliary proteins Pkd1 and BBS12 also resulted in enhanced adipogenesis while inhibition of the IFT anterograde molecular motor Kif3a impaired adipocyte differentiation [136,137].…”
Section: Adipogenesis Defects In the Etiology Of The Bbs Related Obesitymentioning
confidence: 99%
“…However, a study comparing BBS patients with BMI-matched controls showed that the former present better glucose tolerance, thus hinting at potentially important differences between BBS-related and common obesity [138]. Marion and colleagues showed that knockdown of BBS12 in hMSCs results in increased adipogenesis that is accompanied by increased expression of the insulin receptor (IR) and GLUT4, increased localization of GLUT4 to the plasma membrane, and overall increased glucose absorption, and Bbs12 À/À animals present increased insulin sensitivity, improved glucose metabolism and reduced inflammation [136]. Importantly, since adipocytes secrete leptin in response to insulin and glucose, the increased glucose absorption and the overall increased adipogenesis are likely to contribute to the hyperleptinemia that characterize BBS [21,138].…”
Section: Adipogenesis Defects In the Etiology Of The Bbs Related Obesitymentioning
confidence: 99%
“…In addition, the effect on the level of hyperplasia and hypertrophy may differ per gene. By studying Bbs12-knockout mice (144) , it was observed that those mice had a higher number of small-sized to normal-sized adipocytes between hypertrophic cells than the wild-type mice. As small adipocytes are supposed to have a more healthy metabolic activity (152) , this was seen as a possible explanation for the low risk of BBS12 patients to develop type 2 diabetes, whereas in Alström syndrome early-onset type 2 diabetes is common (20,153) .…”
Section: A Primary Cilium For Adipogenesismentioning
confidence: 99%
“…Ciliary proteins may influence either one or both of these forces, and have therefore been referred to as gatekeepers of adipocyte differentiation (144) . Marion et al (144) showed that the reduced expression of the BBS12 gene in mesenchymal stem cells down-regulated the anti-adipogenic pathways but promoted the pro-adipogenic factors. On the other hand, a decrease in Alms1, Ift88 or Kif3a expression inhibits cilium formation, as well as also adipocyte differentiation in mouse 3T3-L1 cells (145,146) .…”
Section: A Primary Cilium For Adipogenesismentioning
confidence: 99%